Distribution patterns of meiofauna on a tropical macrotidal sandy beach, with special focus on nematodes (Caixa d’Água, Amazon Coast, Brazil) (Brazilian Journal of Oceanography, 2019)
Spatial distribution patterns (both horizontal and vertical) of meiofauna, with special focus on nematodes, on a tropical macrotidal beach across different climatic periods were analyzed in this study. Samplings were carried out at five stations in the intertidal zone in June (rainy season) and December (dry season), 2011. At each station, three samples were taken using a corer with 3cm diameter, which was thrust 10cm into the substrate and stratified in 0-2, 2-5, and 5-10cm. Meiofauna was comprised of 16 groups and Nematoda was the dominant. Meiofauna density during rainy season was higher at the central intertidal station and during dry season it was lower near the high tide mark, followed by an increasing trend towards the low tide mark. Meiofauna was more concentrated in the upper sediment layer during rainy season. However, during dry season, the highest density occurred in the lower sediment layer at both stations near the high tide mark. Nematoda association was comprised of 72 genera, with Daptonema and Theristus (both from the family Xyalidae) as the dominant ones in most stations and strata. The genera richness and diversity increased towards the low tide mark, with lower richness in the upper stratum at most stations. Non-selective deposit-feeders predominated during rainy season, while at dry season there was an alternation of dominance between non-selective deposit-feeders and epistrate feeders. Significant differences were found in the meiofauna community, as well as in the Nematoda association in regard to the months, stations, and sediment layers. The distribution patterns of interstitial organisms found in this study, in part, follow what is already known for microtidal beaches but other differential aspects were observed even if compared to environments of macrotidal beaches in temperate regions.